Taxonomic composition of mollusks collected from the stomach content of Astropecten brasiliensis (Echinodermata: Asteroidea) in Santa Catarina, Brazil - Caregnato, Fernanda Freitas; Wiggers, Fábio; Tarasconi, José Carlos; Veitenheimer-Mendes, Inga Ludmila (Revista Brasileira de Biociências, 2009)
The stomach content of 58 individuals of Astropecten brasiliensis Müller & Troschel, 1842, trawled by commercial shrimp vessels in Santa Catarina (Brazil), revealed that this starfish feeds upon a variety of mollusk species. A total of 542 mollusk specimens were found in the stomach content and classified into 24 families, 32 genera, and 35 species. The mollusks were usually well preserved and intact, which facilitated their correct identification. Bivalves and gastropods accounted for 72% and 27% of the mollusks collected in the stomachs, respectively. Three mollusk species (Corbula caribaea, Transenella stimpsoni, and Natica pusilla) occurred most frequently in the stomach content, for all sampling periods, locations, and size classes of starfish. Statistical analysis revealed that the average number of individual mollusks found in the stomachs of A. brasiliensis was higher during the warmer periods.